PENERAPAN PEMBINAAN INTENSIF DALAM PELATIHAN GERAK DASAR TARI MINANGKABAU DI SMP ADABIAH PADANG (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of intensive coaching, and it results in basic movement training for Minangkabau dance at SMP Adabiah Padang. The study is motivated by the still low mastery of basic Minangkabau dance movements among students, which is shown by difficulties in remembering various movements, performing techniques correctly, coordinating body movements, and a lack of confidence in dancing. This research uses a qualitative method with a descriptive approach. Data was collected through observation, interviews, and documentation, and then analyzed through the stages of data collection, data reduction, data presentation, and drawing conclusions. The research results show that intensive training is applied through identifying initial abilities, demonstrating movements, gradual practice, repetitive drills, individual guidance, providing feedback, and ongoing evaluation. Applying this training has positive effects on students' abilities, such as improved mastery of basic Minangkabau dance movements, the ability to remember movement sequences, accuracy in technique, coordination, and self-confidence. Mastering these basic movements becomes a foundation for students to apply them in the Syofyani Pasambahan Dance until they can perform the dance according to the training goals. Therefore, intensive training can be an effective strategy for improving mastery of basic Minangkabau dance movements in extracurricular dance activities at SMP Adabiah Padang.